2019
DOI: 10.3390/ijms20215348
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Protein from Nectria haematococca Induces Apoptosis in Lung Cancer Cells via the P53 Pathway

Abstract: Our previous research has shown that a fungal immunomodulatory protein from Nectria haematococca (FIP-nha) possesses a wide spectrum of anti-tumor activities, and FIP-nha induced A549 apoptosis by negatively regulating the PI3K/Akt signaling pathway based on comparative quantitative proteomics. This study further confirmed that the anti-lung cancer activity of FIP-nha was significantly stronger than that of the reported LZ-8 and FIP-fve. Subsequently, 1H NMR-based metabolomics was applied to comprehensively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In our study, we demonstrated that a seven immune-related lncRNA can improve prognosis prediction in LUAD. Gene set enrichment analysis analysis revealed that these lncRNAs were enriched in the pathways of “P53_SIGNALING_PATHWAY,” “DNA_REPLICATION,” “CELL_CYCLE,” “SMALL_CELL_LUNG_CANCER,” and “PATHWAYS_IN_CANCER,” A recent study illustrated that an immune regulatory protein can induce apoptosis of lung carcinoma cells through the P53 signaling pathway ( 45 ). The P53 signature pathway is closely connected to the progression of lung carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we demonstrated that a seven immune-related lncRNA can improve prognosis prediction in LUAD. Gene set enrichment analysis analysis revealed that these lncRNAs were enriched in the pathways of “P53_SIGNALING_PATHWAY,” “DNA_REPLICATION,” “CELL_CYCLE,” “SMALL_CELL_LUNG_CANCER,” and “PATHWAYS_IN_CANCER,” A recent study illustrated that an immune regulatory protein can induce apoptosis of lung carcinoma cells through the P53 signaling pathway ( 45 ). The P53 signature pathway is closely connected to the progression of lung carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…FIP-fve suppresses lung cancer cell proliferation via p53 activation ( Chang et al, 2013 ). In early studies, we confirmed that FIP-nha induced A549 cell apoptosis by activating p53, which then negatively regulating the PI3K-Akt-mTOR and/or AMPK pathway and causing subsequent metabolic disturbance of A549 cells ( Xie et al, 2018 , Wang et al, 2019 ). In this study, for the first time we deeply explored the mechanism of FIP-nha on GC cells and confirmed that FIP-nha inhibited GC cell proliferation by blocking the EGFR/STAT3/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, GSEA was employed to screen for signaling pathways associated with 13 mitochondria-related lncRNA models, and the results indicated that these signaling pathways were associated with several cellular life activities. The P53 signaling pathway is closely associated with apoptosis and progression of the lung cancer cells (Wang, et al 2019) and it is seen to regulate the immune responses (Muñoz-Fontela et al 2016). Hence, the 13-mitochondria-associated lncRNA model that was constructed in this study was seen to be involved in a few cancer-related signaling pathways.…”
Section: Discussionmentioning
confidence: 95%